Clinical outcomes in percutaneous coronary interventions with polymer-free vs. durable-polymer stents: a metanalysis of randomized clinical trials. (14th October 2021) - Escribano, D; Cordero, A; Bertomeu-Gonzalez, V; Moreno-Arribas, J; Monteagudo, M; Lopez Ayala, J M; Perez-Berbell, P; Quintanilla, M; Zuazola, P
Abstract: Background: Polymer-free (PF) stents were designed as an alternative to durable-polymer (DP) drug-eluting stents to minimize the time on dual antiplatelet treatment for patients at high-risk of bleeding. Nonetheless, the efficacy and safety of PF vs. DP stents in patients undergoing percutaneous coronary intervention (PCI) remain controversial. Methods: We performed a metanalysis with currently available studies that assessed the effect of PF-stents vs. DP-stents after performing a systematic search. The endpoints analyzed were all-cause death, myocardial infarction, target lesion revascularization (TLR) and probable or definite stent thrombosis. The raw numbers of incident end-points reported in each study were used. We performed analyses in short and long term (<1 or >1 year follow-up) studies. Results: We included 12464 patients from 8 studies (5 short-term and 3 long-term): 6723 treated with PF-stents and 5741 with DP stents. Females represented 23.3% (n=3284) and 33.7% (n=4202) were included in the setting of acute coronary syndromes. As shown in the figure, PF-stents were associated to lower incidence of all-cause mortality (HR: 0.91 95% CI 0.84–0.98; p=0.016) and TLR (HR: 0.88 95% CI 0.80–0.96; p=0.003). No differences were observed in the risk of cardiovascular death (HR: 0.96 95% CI 0.86–1.06 p=0.415), myocardial infarction (HR: 0.90 95% CI 0.80–1.01; p=0.061) or probable-definite stent thrombosis (HR: 0.92 95% CI 0.74–1.14; p=0.447). Finally, no differences in the primary end-point (HR: 0.92 95% CI 0.83–1.03; p=0.143) were detected with PF-stents vs. DP-stents. No significant heterogenicity was observed in any of the endpoints, except for the incidence of stent thrombosis. Conclusions: Under current PCI techniques the use of PF-stent might be associated to better outcomes, especially in terms of all-cause mortality and TLR. FUNDunding Acknowledgement: Type of funding sources: None.